Restricting the Market for Quota: An Analysis of Tobacco Production Rights with Corroboration from Congressional Testimony - Rucker, Randal R.; Thurman, Walter N.; Sumner, Daniel A. (Journal of Political Economy, 1995)
Regulatory programs that restrict output levels often impose restrictions on the transfer of rights to produce or to use particular inputs. In this paper, we use a unique cross-section, time-series data set from North Carolina to quantify the welfare effects of transfer restrictions for poundage quota under the U.S. flue-cured tobacco program. We find that the deadweight costs of such restrictions are small but that the distributional effects are substantial. We analyze congressional testimony on quota transfer legislation and conclude that our estimates of the distributional effects are consistent with expressed views of market participants.